1980
DOI: 10.1161/01.str.11.6.606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypertension on blood-brain barrier. Change after restoration of blood flow in post-ischemic gerbil brains. An electronmicroscopic study.

Abstract: SUMMARYThe effect of induced hypertension on the blood-brain barrier (BBB) change in Mongolian gerbils exposed to various periods of ischemia was studied. EVANS blue dye was used to determine the BBB change In animals subjected to different levels of hypertension after 3 h ischemia. Horseradish peroxidase (HRP) was used in electronmicroscopic studies of animals subjected to 30 min, 1,3 or 6 h ischemia and subsequently exposed for 30 min to varying periods and sequences of nonno-and hypertension. Furthermore, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 29 publications
(7 reference statements)
1
24
1
Order By: Relevance
“…We expected the brain of renal failure mice to be more vulnerable to Gd exposure because of hypertension. 20,21 However, we found no significant difference in the Gd concentration in the Gd-DTPA-BMA group between normal mice and mice with renal failure, while the Gd retention at 3d in the Gd-DOTA group was higher in normal mice than in mice with renal failure.…”
Section: Discussioncontrasting
confidence: 55%
“…We expected the brain of renal failure mice to be more vulnerable to Gd exposure because of hypertension. 20,21 However, we found no significant difference in the Gd concentration in the Gd-DTPA-BMA group between normal mice and mice with renal failure, while the Gd retention at 3d in the Gd-DOTA group was higher in normal mice than in mice with renal failure.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast, labeling of the endothelium via IB4 regularly reveals structural alterations affecting the surface of the endothelial layer, which is likely responsible for the observed breakdown of the BBB. Interestingly, this concept of a transendothelial extravasation has already been described in early studies of ischemia 36,37 and was later mostly neglected in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…The uptake of the peripheral peptide as well as other molecular species by the brain might depend on a compromised BBB, as ageing and neurodegenerative diseases are known to contribute to BBB impairment [36]. Changes in the BBB permeability also occur in vascular diseases, hypertension and stroke, all of which represent a risk factor for AD [37,38]. Furthermore, it has been suggested that under normal conditions, clearance of Aß occurs at the BBB and that deficiency in this pathway may contribute to amyloid deposition formation in AD [39].…”
Section: Discussionmentioning
confidence: 99%